Outcomes of allogeneic stem cell transplantation among patients with acute myeloid leukemia presenting active disease: Experience of a single European Comprehensive Cancer Center - De-Mello,Ramon Andrade Bezerra (2016)
Summary Introduction: Allogeneic hematopoietic stem cell transplantation (ASCT) representes a potentially curative approach for patients with relapsed or refractory acute myeloid leukemia (AML). We report the outcome of relapsed/refractory AML patients treated with ASCT. Method: A retrospective cohort from 1994 to 2013 that included 61 patients with diagnosis of relapsed/refractory AML. Outcomes of interest were transplant-related mortality (TRM), incidence of acute and chronic graft-versus-host disease (GVHD), relapse incidence, progression-free survival (PFS) and overall survival (OS). Statistical significance was set at p<0.05. Results: The median age was 61 years (range 1 to 65). The cumulative incidence of 90 days, 1 year, and 3 years TRM were 60%, 26.7%, and 13.3%, respectively (p<0.001). The incidence of relapse was 21.7% at 1 year, 13% at 3 years, and 8.7% at 5 years. Median OS was estimated to be 8 months (95CI 3.266-12.734) and median PFS, 3 months (95CI 1.835-4.165). Conclusion: In our cohort, TRM in first years after ASCT remains considerable, but ASCT in this setting seems to be a good choice for AML patients with active disease. However, novel approaches are needed to reduce TRM and relapse in this set of patients.